Sistema para o estudo do limiar de percepção de corrente elétrica com forma de onda arbitrária. - Henrique Resende Martins (2008)
During the 80's, an instrument to evaluate the psychophysical sensitivity using electric sinusoidal current stimulation had been proposed, which established a relation between fibers diameters and stimulus frequency: 5 Hz for non-myelinated fibers, 250 Hz for thin myelinated fibers and 2 kHz for thick myelinated fibers. One of the problems encountered on neuroscience researches is that there is not appropriate device that allows the use of others frequencies and others waveforms. For this reason, it is difficult to perform deeper studies into somatosensory electrical stimulation. Therefore, this work aims to develop a medical device to Current Perception Threshold using an arbitrary waveform. The prototype was developed using the ADSP-BF533 evaluate board (ADSP-BF533 EZ-KIT Lite, Analog Devices, Inc.). It was used for performing mathematical algorithms that generate several stimuli waveforms and determine the perception threshold. A current source voltage controlled that uses a class AB power output stage was developed to generate stimulus with constant current intensity into 2 Hz and 5 kHz. The maximum current intensity is 8 mA and resolution equal to 8 ?A. The system is controlled by a GUI (Graphical User Interface) software, which allows setting the waveform parameters and stimulation protocol. Moreover, the user will be able to implement an arbitrary waveform. Tests of the system demonstrate that it could be used for the determination of perception threshold to electric current. On a near future, it is expected that the system can assist in diagnoses of neuropathies, thus improving the health and quality life of the people.